Quality and adequacy of duck patties stored at ambient and refrigeration temperature - Shan Kishore; Roshen Akshay; Narayana Singh (Advances in Aquaculture and Fisheries Management, 2019)
Effect of storage periods at ambient and refrigeration temperature on duck patties was studied. pH of duck patties significantly increased (P < 0.01) at ambient temperature and decreased (P < 0.01) at refrigeration temperature. TBA and Tyrosine values increased significantly (P < 0.01) with increased storage period at both temperatures. A higher rate of increase in TBA values occurred at ambient temperature than refrigeration temperature. There was no significant difference in proximate composition except moisture content on different storage periods at both temperatures. TVC and TPSC values increased significantly (P < 0.01) with increase in storage period at both temperatures. A significant decrease in scores of organoleptic evaluation occurred with increase in storage period at both temperatures. A higher rate of decrease in sensory scores occurred at ambient temperature than that of refrigeration temperature. A significant correlation of physicochemical changes with acceptability of duck patties was noticed. So, duck patties were acceptable upto 7 days at refrigeration temperature.